Cardiovascular Risk Score, Cognitive Decline, and Dementia in Older Mexican Americans: The Role of Sex and Education. Issue 2 (22nd April 2013) - Hazzouri, Adina Zeki Al; Haan, Mary N.; Neuhaus, John M.; Pletcher, Mark; Peralta, Carmen A.; López, Lenny; Pérez Stable, Eliseo J.
Abstract : Background: The purpose of this study was to examine the associations of cardiovascular disease (CVD) risk with cognitive decline and incidence of dementia and cognitive impairment but not dementia (CIND) and the role of education as a modifier of these effects. Methods and Results: One thousand one hundred sixteen Mexican American elderly were followed annually in the Sacramento Area Latino Study on Aging. Our sex‐specific 10‐year CVD risk score included baseline age, systolic blood pressure, total cholesterol, high‐density lipoprotein, smoking, body mass index, and diabetes. From adjusted linear mixed models, errors on the Modified Mini–Mental State Exam (3MSE) were annually 0.41% lower for women at the 25th percentile of CVD risk, 0.11% higher at the 50th percentile, and 0.83% higher at the 75th percentile ( P value of CVDrisk×time <0.01). In men, 3MSE errors were annually 1.76% lower at the 25th percentile of CVD risk, 0.96% lower at the 50th percentile, and 0.12% higher at the 75th percentile ( P value of CVDrisk×time <0.01). From adjusted linear mixed models, the annual decrease in the Spanish and English Verbal Learning Test score was 0.09 points for women at the 25th percentile of CVD risk, 0.10 points at the 50th percentile, and 0.12 points at the 75th percentile ( P value of CVDrisk×time=0.02). From adjusted Cox models in women, compared with having <6 years of education, having 12+ years of education was associated with a 76% lower hazard of dementia/CIND (95% CI, 0.08 to 0.71) at the 25th percentile of CVD risk and with a 45% lower hazard (95% CI, 0.28 to 1.07) at the 75th percentile ( P value of CVDrisk×education=0.05). Conclusions: CVD risk score may provide a useful tool for identifying individuals at risk for cognitive decline and dementia.